Estimating the Un-sampled pH Value via Neighbouring Points Using Multi-Layer Neural Network - Genetic Algorithm - Aziz, Muhammad Aznil Ab; Abas, Mohammad Fadhil; Ali, Muhamad Abdul Hasib; Saad, Norhafidzah Mohd; Ariff, Mohd Hisyam Mohd; Bashrin, Mohamad Khairul Anwar Abu (2023 19th IEEE International Colloquium on Signal Processing & Its Applications (CSPA), 2023)
This study shows a new method to estimate unsampled pH value by utilizing neighboring pH, which according to recent literature, has not been done yet. In investigating this method, three algorithms are used: Neural Network-Genetic Algorithm (MLNN-GA), MLNN with backpropagation (MLNN-BP), and averaging method. MLNNGA and MLNN-BP are inputted with four pH values from distant adjacent locations on a similar basin. MLNN-GA and MLNN-BP utilize GA and backpropagation respectively to update the weight. GA optimizer is used in MLNN-GA where the result of each learning weight will be the initial weight of the next learning process. All three methods are compared based on RMSE, MSE and MAPE. MLNN-GA yielded the lowest average RMSE =0.026265, average MSE =0.000886 and average MAPE =0.003985 compared to MLNN-BP (average RMSE =0.042644, average MSE =0.002648, average MAPE =0.006862) and averaging method (average RMSE =0.136629, average MSE = 0.026128, average MAPE =0.150400). Noticeably, estimating unsampled pH value utilizing neighboring pH by using MLNNGA shows a better performance than MLNN-BP and averaging method.